Consensus statement for perioperative care in total hip replacement and total knee replacement surgery: Enhanced Recovery After Surgery (ERAS®) Society recommendations. (2nd January 2020) - Wainwright, Thomas W; Gill, Mike; McDonald, David A; Middleton, Robert G; Reed, Mike; Sahota, Opinder; Yates, Piers; Ljungqvist, Olle
Abstract : Background and purpose — There is a large volume of heterogeneous studies across all Enhanced Recovery After Surgery (ERAS ® ) components within total hip and total knee replacement surgery. This multidisciplinary consensus review summarizes the literature, and proposes recommendations for the perioperative care of patients undergoing total hip replacement and total knee replacement with an ERAS program. Methods — Studies were selected with particular attention being paid to meta-analyses, randomized controlled trials, and large prospective cohort studies that evaluated the efficacy of individual items of the perioperative treatment pathway to expedite the achievement of discharge criteria. A consensus recommendation was reached by the group after critical appraisal of the literature. Results — This consensus statement includes 17 topic areas. Best practice includes optimizing preoperative patient education, anesthetic technique, and transfusion strategy, in combination with an opioid-sparing multimodal analgesic approach and early mobilization. There is insufficient evidence to recommend that one surgical technique (type of approach, use of a minimally invasive technique, prosthesis choice, or use of computer-assisted surgery) over another will independently effect achievement of discharge criteria. Interpretation — Based on the evidence available for each element of perioperative care pathways, the ERAS ® Society presents a comprehensive consensus review, for the perioperative care of patients undergoing total hip replacement and total knee replacement surgery within an ERAS ® program. This unified protocol should now be further evaluated in order to refine the protocol and verify the strength of these recommendations.